Body over troubled waters - Swanson, Denise (Swanson, Denise. Welcome back to Scumble River, 2021)
"School psychologist Skye Denison-Boyd is settling into the rhythm of being a working mom, but when school is put on lockdown, life gets messy again. Not only is she stuck in a room with her horrible superintendent, Dr. Wraige, it looks like the lockdown was a false alarm-someone left a cupid's bow and arrow in a classroom. Later, as Wally looks into an attempted break-in, he finds the superintendent murdered, his jugular cut with the arrow of a Cupid statue. Did love just turn deadly in Scumble River? As the part-time psychological consultant for the police department, Skye joins Wally in investigating the murder. But things get even more personal when her godfather Uncle Charlie gets wrapped up in a state police sting. With a dead boss, a godfather under suspicion, and a mythical killer on the loose, Skye has more than enough work cut out for her!"--